2018
DOI: 10.1371/journal.pone.0191482
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus induces HLA-class-II-restricted alloreactivity in an acute myeloid leukemia cell line

Abstract: Cytomegalovirus (HCMV) reactivation is found frequently after allogeneic hematopoietic stem cell transplantation (alloSCT) and is associated with an increased treatment-related mortality. Recent reports suggest a link between HCMV and a reduced risk of cancer progression in patients with acute leukemia or lymphoma after alloSCT. Here we show that HCMV can inhibit the proliferation of the acute myeloid leukemia cell line Kasumi-1 and the promyeloid leukemia cell line NB4. HCMV induced a significant up-regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Since HCMV can modulate interferon gamma signaling (19,23), this may be one way of decreasing promoter IV CIITA transcripts. Coculturing infected Kasumi-1 cells with uninfected peripheral blood mononuclear cells resulted in an increase in HLA-DR transcript levels, illustrating the complexity of the HCMV-mediated regulation of MHC class II under different conditions (59). Importantly, our results focus on the endogenous regulation of MHC class II and show that HCMV downregulates the expression of CIITA by decreasing transcription from promoter III, resulting in decreased HLA-DR␣ transcripts and MHC class II surface expression.…”
Section: Discussionmentioning
confidence: 65%
“…Since HCMV can modulate interferon gamma signaling (19,23), this may be one way of decreasing promoter IV CIITA transcripts. Coculturing infected Kasumi-1 cells with uninfected peripheral blood mononuclear cells resulted in an increase in HLA-DR transcript levels, illustrating the complexity of the HCMV-mediated regulation of MHC class II under different conditions (59). Importantly, our results focus on the endogenous regulation of MHC class II and show that HCMV downregulates the expression of CIITA by decreasing transcription from promoter III, resulting in decreased HLA-DR␣ transcripts and MHC class II surface expression.…”
Section: Discussionmentioning
confidence: 65%
“…Although somewhat controversial, a number of human clinical studies have demonstrated an association between HCMV reactivation following bone marrow transplantation and reduced relapse rates of leukemias and lymphomas [89][90][91]. Multiple mechanisms are thought to be at play in these cases related to the known effects of CMV on activation of NK cells [92], CD8 + T cells and γδ T cells [89] as well as the potential for both direct and immunostimulatory oncolytic effects [93].…”
Section: Cmv-specific Cd8 + T Cells: the Link Between CMV Infection Amentioning
confidence: 99%
“…In healthy individuals, HCMV infection is generally asymptomatic, although HCMV can cause acute infectious mononucleosis (2,3) and has also been linked to chronic inflammatory diseases, such as atherosclerosis, and cancers, including glioblastoma and colon cancer (4,5). In contrast, HCMV infection of immunocompromised individuals, including AIDS patients and transplant recipients, causes severe morbidity and mortality (6)(7)(8). HCMV is also the most common congenital infection occurring in approximately 20,000 to 30,000 infants each year in the United States, with approximately 10 to 15% of infected newborns developing permanent neurological abnormalities (9).…”
mentioning
confidence: 99%